Two new species of Glodianus Cameron and Hylophasma Townes (Hymenoptera: Ichneumonidae: Cryptinae) from Mexico - Kasparyan, Dmitry R.; Khalaim, Andrey I. (Zootaxa, 2024)
Three Mexican species of the genus Glodianus Cameron and five Mexican species of Hylophasma Townes are briefly reviewed. Two species, Glodianus rufithorax sp. nov. and Hylophasma aterrima sp. nov., are described as new to science, and G. graciliventris (Cameron) is resurrected from synonymy with G. delectus (Cresson) (sp. resurr.). Identification keys to all ten world species of Glodianus and all seven world species of Hylophasma are given.